Invasion of trophoblast cell lines is inhibited by miR-93 via MMP-2. (May 2017) - Pan, Qiong; Niu, HuiYuan; Cheng, LongFei; Li, XiaoQiong; Zhang, QiGang; Ning, Ying
Abstract: Preeclampsia (PE) is a serious pregnancy-related syndrome, which is characterized by gestational hypertension and proteinuria. The microRNA-93 (miR-93) is upregulated in the maternal plasma of patients with PE. However, the functional role of miR-93 in PE remains unknown. Here, we identified that miR-93 inhibits trophoblastic invasion, which is correlated with PE development. In immortalized trophoblast cell lines, transwell assay showed that miR-93 mimics significantly inhibited the migration and invasion of immortalized trophoblast cells, whereas miR-93 inhibitors significantly promoted cell migration and invasion. Moreover, luciferase assays confirmed that miR-93 directly bound to the 3'untranslated region of matrix metalloproteinase-2 (MMP-2), and western blotting showed that miR-93 suppressed the expression of MMP-2 at the protein levels. This study indicated that miR-93 inhibits MMP-2 and reduces migration and invasion of immortalized trophoblast cells. Thus, miR-93 may represent a potential therapeutic target for PE intervention. Highlights: miR-93 mimics inhibit the migration and invasion of immortalized trophoblast cells. miR-93 inhibitors promote the migration and invasion of immortalized trophoblast cells. miR-93 targets 3′ UTR of MMP-2 in immortalized trophoblast cells. miR-93 inhibits MMP-2 in immortalized trophoblast cells.